Batak Toba Ethnic in Indonesia as a Locus Theologicus: Exploring the Spiritual, Wisdom and Aesthetic Values of Ragi Idup Ulos - Edison Robertus Lamarsen Tinambunan (Asosiasi Ahli Filsafat Keilahian Indonesia, 2023)
Batak Toba is one of many ethnic groups in Indonesia that reside around Lake Toba and are now scattered worldwide. Since the colonial period, this group has become a target for Protestant Christian missions and Catholics, who make it a “locus theologicus” based on their respective characteristics. One tradition of Batak Toba is ulos, such as “ragi idup”, which holds religious, wisdom, and aesthetic meanings. This study examines “ragi idup” ulos as a “locus theologicus” through its spiritual values rooted in wisdom and civilization. The meaning to be achieved in this paper is that the wearing and giving of ulos “ragi idup” is the warning and giving of wisdom in life. Qualitative methods and interviews with knowledgeable individuals help identify religious and wisdom values that can bring theology together using a symbolic approach.